The politics of contemporary collecting in Aotearoa New Zealand : examining shifts in museum policies and practices from the 1981 Springbok tour to COVID-19 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies at Te Kunenga ki Pūrehuroa Massey University, Te Papa-i-Oea Palmerston North, New Zealand - Claasen, April Charlotte Jane (Massey University, 2024)
Museums are more than repositories of material culture; they are active participants in shaping collective memory and negotiating societal norms. This thesis examines the evolving collecting practices of New Zealand museums during two pivotal national events: the 1981 Springbok Tour and the COVID-19 pandemic. Through these case studies, it explores how museums navigate power dynamics, ethical challenges, and community expectations in their curatorial decisions. Drawing on Bourdieu’s concepts of cultural capital and habitus, and Foucault’s theories of power, governmentality, and surveillance, this research interrogates the tensions between institutional authority and community engagement. The analysis traces a shift from reactive approaches during the Springbok Tour, shaped by dominant political pressures, to the proactive, community-focused collecting strategies employed during the COVID-19 pandemic. This shift highlights an ongoing negotiation between preserving institutional priorities and representing diverse societal voices. Using a mixed-methods approach—including interviews, archival research, and survey data— this thesis argues that curatorial decisions are never neutral but are shaped by institutional frameworks and the politics of memory. It advocates for reflexive and collaborative collecting practices that decentralise dominant narratives, fostering inclusivity and equity in documenting Aotearoa’s histories. Ultimately, this study situates museum collecting within the broader dynamics of power, responsibility, and ethics, offering insights into how museums can engage meaningfully with their communities while responding to the complexities of contemporary society.
Figure 3.1 was removed for copyright reasons. Figures 3.3, 3.4, 3.5 and 3.6 are reproduced with permission. Figures 4.1, 4.3, 4.5 and 4.6 are reused under a Creative Commons CC BY-NC-ND licence.
Keywords: 430202 Critical heritage, museum and archive studies; 430320 New Zealand history